Ageratina adenophora causes spleen toxicity by inducing oxidative stress and pyroptosis in mice. Issue 7 (24th July 2019) - Sun, Wei; Zeng, Chaorong; Yue, Dong; Liu, Shanshan; Ren, Zhihua; Zuo, Zhicai; Deng, Junliang; Peng, Guangneng; Hu, Yanchun
Abstract : Ageratina adenophora is an invasive weed with potent toxicological effects on livestock. Oxidative stress and pyroptosis play a pivotal role in regulating animal or human health and disease. The object of this study was to determine the mechanism underlying splenic toxicity induced by A. adenophora in a mouse model. Ageratina adenophora significantly increased the levels of reactive oxygen species and malondialdehyde, but decreased the antioxidants like catalase, superoxide dismutase, glutathione and glutathione peroxidase. In addition, the activity of the antioxidant enzymes was also decreased upon A. adenophora treatment. The induction of the pyroptosis pathway was evaluated in terms of the expression levels of Nod-like receptor protein 3, nuclear factor-κB, caspase-1, gasdermin-D and interleukin-1β, all of which were significantly elevated by A. adenophora . These findings suggest that A. adenophora impairs spleen function in mice through oxidative stress damage and pyroptosis.